Targeting the viral Achilles' heel: recognition of 5'-triphosphate RNA in innate anti-viral defence. - Rehwinkel, J; Reis e Sousa, C (2013)
Some RNA virus genomes bear 5'-triphosphates, which can be recognized in the cytoplasm of infected cells by host proteins that mediate anti-viral immunity. Both the innate sensor RIG-I and the interferon-induced IFIT proteins bind to 5'-triphosphate viral RNAs. RIG-I signals for induction of interferons during RNA virus infection while IFITs sequester viral RNAs to exert an anti-viral effect. Notably, the structures of these proteins reveal both similarities and differences, which are suggestive of independent evolution towards ligand binding. 5'-triphosphates, which are absent from most RNAs in the cytosol of uninfected cells, are thus a marker of virus infection that is targeted by the innate immune system for both induction and execution of the anti-viral response.